2003
DOI: 10.1136/jim-51-04-24
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hyperbaric Oxygen on Proliferative and Apoptotic Activities and Reactive Oxygen Species Generation in Mouse Fibroblast 3T3/J2 Cell Line

Abstract: Collectively, our findings allow us to conclude that (1) all of the exposure periods to HBO at 1.0 ATA or 30- and 60-minute periods at 2.5 ATA enhance cell growth, (2) 120-minute exposure to HBO at 2.5 ATA exerts a marked proapoptotic effect, and (3) no evident relationships occur between the effects of HBO on cell growth and ROS production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 0 publications
2
33
1
Order By: Relevance
“…However, an enhanced generation of both intracellular and extracellular ROS was observed after a 24-hour exposure. This finding seems to be consistent with another study that found an increase of ROS production in 3T3/J2 fibroblasts exposed to HBOT [8], where it was suggested that intracellular ROS generation could be directly related to cell apoptosis.…”
Section: Discussionsupporting
confidence: 93%
“…However, an enhanced generation of both intracellular and extracellular ROS was observed after a 24-hour exposure. This finding seems to be consistent with another study that found an increase of ROS production in 3T3/J2 fibroblasts exposed to HBOT [8], where it was suggested that intracellular ROS generation could be directly related to cell apoptosis.…”
Section: Discussionsupporting
confidence: 93%
“…HBO also attenuates microvascular dysfunction and reperfusion microvascular ischemia, as demonstrated in both experimental models and patients with acute myocardial infarction [5]. Since molecular oxygen is one of the critical nutrients and plays a central role in the reparative process of wound [6], the beneficial effects of HBO in treating ischemia-related wounds may be mediated by stimulating collagen synthesis [7], cell proliferation [8][9][10][11], and promoting angiogenesis [12][13][14]. However, the mechanism(s) accounting for HBO-induced vessel formation is still not well documented.…”
Section: Introductionmentioning
confidence: 99%
“…Although the mechanism of tumor cell suppression by uncombined HBO treatment remains unclear in detail, it has been reported that cell damage due to reactive oxygen species (ROS) or free radicals plays a role in mediating this effect of HBO (29). More specifically, tumor cells are destroyed if ROS level rises beyond the limit of a tumor's resistance to oxidative stress following treatment with HBO.…”
Section: Discussionmentioning
confidence: 99%